Cultural Exports, Creative Strategies and Collaborations in the Mainland Chinese Market - Keane, Michael; Yecies, B. (Springer Nature, 2018)
The authors examine how Chinese film and television companies have collaborated with their counterparts in South Korea during the past decade. The first part of the chapter challenges the concept of cultural and media ‘flows’, arguing that processes and technologies have probably been more instrumental in transforming the Chinese media industries. Whereas the generic term ‘flows’ applies to finished content, an increase in film co-production and formatting activity in the television industry between the two nations leads us to examine other factors including professional relationships and the exchange of creative ideas and technology. The next section looks at the Chinese government’s ‘going out’ strategy through the 2014 film co-production agreement with South Korea, and the post-production collaboration that followed it. We then examine some examples of television collaboration and how this is helping to raise China’s profile in East Asia, where it is inevitably tarred with the negative image of the Chinese Communist Party. The question that arises is: will such East Asian collaboration efforts enable or impede China’s media dream of reaching out to the world stage?